The Website Development of a Teacher Tools Assistance System Integrated of Project Based Learning Model - Wawan Kurniawan; Febri Berthalita Pujaningsih; Abdussalam Aswin Hadist (Postgraduate, University of Mataram, 2025)
The study, conducted in response to the shortcomings of the digital learning system in facilitating the Physics learning process with the project based learning model. So the purpose of this study is to develop a Teacher Tools Assistance System website as an answer to this problem. This study adopts the RnD method with the ADDIE model development framework focused on three stages, namely analysis, design, and development. The analysis stage examines the curriculum and learning environment. At the design stage, a prototype of the Teacher Tools Assistance System website is produced which is then tested at the development stage. The development stage is carried out with various tests, namely the Black-Box test, installation/launch, validation by media experts and material experts, and user responses involving 58 students of SMAN 3 Kota Jambi class XI. As a result, in the Black Box test, the website functionality achieved 100% on the teacher's page and 96% on the student's page. In the media expert validation, the score given was 4.44, which was categorized as very feasible. While the validation by material experts 1 and 2 rated it 4.50 and 4.47, categorizing it as very feasible category. In addition, the response from users gave a score of 4.20 in the category of worthy of the product. However, there are still shortcomings including the appearance of the website, website navigation that is not yet user friendly, and the emergence of bugs.